PEMANFAATAN CONSUMPTION METERSEBAGAI MEDIA KONTROL UNTUK MEWUJUDKANECONO STYLE DALAM BERKENDARA SEPEDA MOTOR - Barry Nur Setyanto, Agus Irawan, dan Muhammad Hidayat (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research is aimed to know the plan, the making process, the performanceand device effectiveness (consumption meter) which can monitor the fuel consumptionof motorcycle. Consumption meter can be used to monitor the fuel consumption, thus themotorcyclist can economize the fuel in riding motorcycle.This research was conducted in two steps; the first step was accuracy test,precious test, range and response of consumption meter which was initiated by themeasurement and the collection of the data to program microcontroller ATMEGA8535.The second step was the test of its effectiveness to two different ways of driving. The firstway was by good treatment that is driving according to the driving standard. The secondway was bad treatment, which is driving not according to the standard. The test of itseffectiveness used three different motorcyclists in order to get the accurate result. Thetest was done twice to good treatment and once to bad treatment.The result of the research shows that the consumption meter functions properlyif road field is smooth and not damaged. When it is tested in the damaged road, therewill be an error in reading the fuel indicator. Thus, the device can only be used if the roadis smooth and relatively flat. The result of effectiveness test conducted with the routejalan Gejayan – jalan Solo - jalan Janti - JEC – jalan Janti – jalan Solo – jalan Gejayanshows that the good attitude in driving will influence the fuel consumption. Given thechange of attitude, the econo style can be done by any motorcyclists.Keyword: Consumption Meter, Rcono style, fuel, motorcycle,